Biofilm Formation and Antibiotic Resistance of Staphylococcus aureus Isolates: Pembentukan Biofilm dan Resistensi Antibiotik pada Isolat Staphylococcus aureus - Al-Khamis, Ahmed Ramadan Hadabi; Abed, Jasim Mohammed; Sameer, Hamid Kadhim; Hassan, Mohammed Ali (Academia Open, 2025)
General Background: Biofilm-associated infections represent a major clinical challenge due to their persistence and resistance to antibiotics. Specific Background: Staphylococcus aureus is a common pathogen implicated in chronic and hospital-acquired infections, particularly due to its biofilm-forming capability. Knowledge Gap: Despite global reports on S. aureus resistance, limited data exist regarding its biofilm formation and antibiotic susceptibility in clinical isolates from Mashhad Hospital. Aims: This study aimed to investigate the prevalence, biofilm formation, and antibiotic resistance profile of S. aureus isolated from hospitalized patients. Results: A total of 150 clinical samples (blood, urine, wounds, and secretions) were collected from 95 male and 55 female patients, yielding 70 S. aureus isolates. All isolates were biofilm-positive. Antibiotic susceptibility testing revealed 100% resistance to ampicillin, 80.3% to azithromycin, and 70.7% to cefoxitin, while all isolates remained sensitive to vancomycin and clarithromycin. Statistical analysis showed significant associations (p < 0.05) between patient sex and both biofilm formation and antibiotic resistance patterns. Novelty: This study provides updated, localized resistance data and highlights the universal biofilm-forming potential of S. aureus in this region. Implications: The findings underscore the need for enhanced infection control strategies and the prudent use of antibiotics to mitigate biofilm-related resistance in hospital settings. Highlights: S. aureus causes resistant, biofilm-related hospital infections. 70 isolates: all biofilm-positive, high resistance to common antibiotics. Requires improved antibiotic stewardship and infection control measures. Keywords: S. aureus, Antibiotic Resistance, Biofilm, Clinical samples